PENINGKATAN KAPASITAS MASYARAKAT MELALUI PROGRAM DESA/ KELURAHAN TANGGUH BENCANA (DESTANA) DI KELURAHAN BUJEL KECAMATAN MOJOROTO KOTA KEDIRI - Fandayati, Inggit; Ficky Adi Kurniawan (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2022)
Bujel Village which is located in Mojoroto District in Kediri City is one of the villages affected by the flood. Geographically, the area of Kediri City which is located between 2 mountains and crossed by the Brantas River has the potential to be affected by the flood disaster. This community capacity building activity through the Disaster Resilient Village program aims to increase the capacity and resilience of the apparatus and community of Bujel Village in dealing with disasters. The method used is a participatory survey method, lectures, discussions, direct practice, observation, community assistance, pretest, posttest and evaluation. The results obtained that there are many benefits from this community capacity building activity and an increase in the score between pretest and posttest with an initial average of 55.75 to 77.5. An increase in score of 21.75.